Uganda - Strengthening the Effectiveness of the Public Investment Program : Public Expenditure Review - World Bank (Washington, DC, 2013)
To advance the effectiveness of Uganda's public investment program (PIP) improvements can and should be made from the inception of an investment program all the way through its implementation. It is not a question of abandoning the current process but one of adjusting the various stages of the current PIP processes in place such that in particular quality at entry and readiness of investment projects improves, contract management gets strengthened, and above all incentives for implementation are enhanced. The aim of the adjustments to the PIP processes in Uganda is to ensure that the PIP can assist the government to direct resources to those investments that provide the highest economic and social return. The government is advised to revisit the current informational content of the PIP as well as the decision making process of the PIP at each of the phases of the PIP, i.e., preparation, evaluation, and implementation. The remainder of the executive summary will discuss how this can potentially be accomplished. Uganda's economy has grown rapidly over the past 20 years propelled by consistent policy reforms. Annual growth in real Gross Domestic Product (GDP) has averaged 7.4 percent over the 10 years ending in 2009/10, compared with 6.5 percent recorded in the 1990s. This acceleration was in spite of consecutive exogenous shocks including: the oil price shock; drought conditions with adverse effects on energy generation and agricultural production; and volatile food prices.